Elevated Plasma Reelin Levels in Children With Autism - Cuchillo-Ibáñez, Inmaculada; Andreo-Lillo, Patricia; Pastor-Ferrándiz, Lorena; Carratalá-Marco, Francisco; Sáez-Valero, Javier (Frontiers in Psychiatry, 2020)
Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders involving age-dependent gene dysregulation. Reelin is a glycoprotein that varies its expression throughout lifetime and controls cortical patterning and synaptogenesis. Brain and plasma reelin levels have been reported to be low in adults with autism; as well as in children with autism, but only when compared to control adults. Therefore, reelin expression levels in children with autism are unclear. For this reason, we compared plasma reelin levels in children with autism and children without autism (non-ASD) of similar ages to evaluate reelin expression in ASD during childhood. Plasma samples from 19 non-ASD (8.9 ± 0.8 years) and 40 children with autism (7.5 ± 0.5 years) were analysed. We found that 50% of the children with autism displayed similar plasma reelin levels to the non-ASD group. However, the remaining 50% expressed more than 30 times more reelin compared to non-ASD levels. We also show that male children with autism displayed significantly higher reelin levels than females. The clinical presentation of this subgroup could not be distinguished from that of children with autism. Epilepsy or ADHD were not associated to reelin levels. We conclude that the high levels of plasma reelin might be an important hallmark in a subset of children with autism, previously unnoticed. As we could not find any correlation between reelin levels and ASD clinical presentations, our results may indicate transient reelin increases in the plasma or the characterization of a group of ASD individuals with a different pathophysiology.